Theta‐gamma coupling and ApoE genotype in patients at risk for Alzheimer's dementia: Developing topics. (7th December 2020) - Patterson, Rachel A; Brooks, Heather J; Zomorrodi, Reza; Kumar, Sanjeev; Blumberger, Daniel M; Graff‐Guerrero, Ariel; Fischer, Corinne E; Flint, Alastair; Herrmann, Nathan; Kennedy, James L; Lanctot, Krista L; Mah, Linda; et al.
Abstract: Background: Theta‐gamma coupling (TGC) is an electroencephalography (EEG) marker of working memory and depends on robust synaptic plasticity within the recurrent prefrontal cortical networks (Rajji et al. 2017, Buszaski et al. 2012). ApoE4 allele has deleterious effects on synaptic plasticity (Teter et al. 2004). Thus, the primary objective of this analysis is to determine whether there is a relationship between ApoE4 genotype and TGC during the performance of a working memory task (N‐back). Method: We used baseline data from a large Alzheimer's dementia prevention trial. Participants were diagnosed with Mild Cognitive Impairment (MCI), past history of Major Depressive Disorder (MDD), or both (MCI+MDD) and had completed N‐back‐EEG and ApoE genotyping. TGC was measured across right and left frontal electrodes. Participants were grouped based on E4 presence (ApoE2/E3 or ApoE3/E3 [noncarriers] vs. ApoE3/E4 or ApoE4/E4 [carriers]). Result: We included 248 participants (MCI= 125; MDD= 44, MCI+MDD= 79; 153 females/95 males). There were 182 ApoE4 noncarriers (age= 71±6.5; Theta power= 16, 290±14, 764; Gamma power= 5793±5663; TGC= 0.00251±0.00227; PiB frontal amyloid=1.4371±0.32) and 66 noncarriers (age=71±5.0; Theta power= 17, 235±14, 312; Gamma power= 6473±5287; TGC= 0.002184±0.001622; PiB frontal amyloid= 2.09±0.78). Multiple linear regression results show that ApoE4 carriers had reduced TGC (β= 0.205, p= 0.042, Cohen's d= 0.28) after controlling for age, sex, diagnosis, theta power, gamma power, and PiB frontal amyloid. Gamma power was also a significant predictor of TGC. Conclusion: Our results suggest that presence of ApoE4 allele contributes to the modulation of TGC during a working memory task. As ApoE impacts synaptic plasticity, our findings suggest that synaptic plasticity or other ApoE‐related mechanisms underlie TGC. Rajji, T.K., et al., Ordering Information in Working Memory and Modulation of Gamma by Theta Oscillations in Humans. Cerebral Cortex, 2017. 27(2): p. 1482‐1490. Buzsaki, G. and X.J. Wang, Mechanisms of Gamma Oscillations, in Annual Review of Neuroscience, Vol 35, S.E. Hyman, Editor. 2012. p. 203‐225. Teter, B., ApoE‐dependent plasticity in Alzheimer's disease. Journal of Molecular Neuroscience, 2004. 23(3): p. 167‐179.